2018
DOI: 10.15171/jcs.2018.004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Two-Staged Warm Compress on the Pain Duration of First and Second Labor Stages and Apgar Score in Prim Gravida Women: a Randomized Clinical Trial

Abstract: Introduction: The aim of this study was to assess the effect of two-stage warm compress technique on the pain duration of the first and second labor stages and neonatal outcomes. Methods: The clinical trial was done on 150 women (75 subjects in each groups) in Shiraz-affiliated hospitals in 2012 A two-staged warm compress was done for 15-20 minutes in the first and second labor phase (cervical dilatation of 7 and 10 cm with zero status) while the control group received hospital routine care. The duration of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 27 publications
1
27
0
2
Order By: Relevance
“…10 Further, this study demonstrated that duration of labour was not reduced in experimental group. Similarly, Akbarzadeh et al, 12 reported that there was no significant difference in the duration of the first stage in the experimental and control group. These findings were contradictory to the study done by Behmanesh et al, 7 where duration of the first stage (P<0.001) and the third stage of labour ( P<0.001) was reduced in experimental group.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…10 Further, this study demonstrated that duration of labour was not reduced in experimental group. Similarly, Akbarzadeh et al, 12 reported that there was no significant difference in the duration of the first stage in the experimental and control group. These findings were contradictory to the study done by Behmanesh et al, 7 where duration of the first stage (P<0.001) and the third stage of labour ( P<0.001) was reduced in experimental group.…”
Section: Discussionmentioning
confidence: 80%
“…10 Heat also helps in vasodilation and thus increasing the flow of blood. 11 Warm compression is very simple to apply with no undesirable effect on mother and fetus 12 as well as help the mother by decreasing labour pain 12 and improve maternal satisfaction, 9 hence investigator used new method that is hydrochollator pack which consist silicon crystals to give warm compression (moist heat) as a nonpharmacological and non-invasive method for three times at the interval of one hour to get relief from labour pain as well as to assess the effect of moist heat for longer duration. The study was conducted with the aim of investigation the effect of moist heat therapy on lumbosacral region on pain of labour, duration of three stages and fetal outcomes in nulliparous mothers.…”
Section: Introductionmentioning
confidence: 99%
“…Within foetal characteristics are higher body weight and foetal position. Intolerable pain in humans results in a high catecholamine release, which leads to less uterine blood perfusion, reduces uterine contractions' effectiveness, and, consequently, prolongs labour [95]. Also, it induces dystocia, exhaustion, and foetal distress, in addition to postpartum posttraumatic stress disorder [5,96,97].…”
Section: Factors Affecting Labour Pain Dystociamentioning
confidence: 99%
“…These responses are hypothesised to produce maternal metabolic acidaemia, foetal acidosis, and dysfunctional labour. Such effects can be mostly harmless in the course of eutocic delivery [95]. However, pain that an individual is unable to control leads to increased release of catecholamines, reduced uterine contractions and the consequent dystocia, fatigue, foetal suffering, and postpartum posttraumatic stress disorder [5,96].…”
Section: Consequences Of Painmentioning
confidence: 99%
See 1 more Smart Citation